A large-scale model of lateral pressure on a buried pipeline in medium dense sand - Alarifi, H. (MDPI AG, 2021)
Modern countries utilise buried pipelines for the long-distance transportation of water, oil, and gas due to their efficiency and continuity of delivery to receiving locations. Due to soil movements such as landslides, excessive earth pressure imposed on buried pipelines causes damage and, consequently, leaking of liquids, gases or other harmful effluents into the soil, groundwater, and atmosphere. By using a large-scale physical model, the lateral pipelineâsoil interaction in sandy soil was researched. This study investigated the stress distribution on a buried pipe induced by lateral soil displacement. The external forces on the buried pipe caused by the surrounding soil motion were measured using earth pressure cells installed in the active zone along the pipeline. Additionally, visual inspection of ground deformation patterns on the surface, including tensile cracks, above a shallow-buried pipeline subjected to lateral soil movement was reported. The results revealed that lateral soil movement has a potency effect on buried pipelines. The findings also indicated that the highest stresses occur at the unstable soil boundaries prior to reaching the soilâs peak strength. After observing the soil surfaceâs rupture, most of the stress increments were concentrated in the middle section of the pipe. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.